2011
DOI: 10.1017/s1743921312012744
|View full text |Cite
|
Sign up to set email alerts
|

GRB 101225A - a new class of GRBs?

Abstract: Abstract. The Christmas burst, GRB 101225A, was one of the most controversial bursts in the last few years. Its exceptionally long duration but bright X-ray emission showing a thermal component followed by a strange afterglow with a thermal SED lead to two different interpretations. We present here our model ascribing this strange event to a new type of GRB progenitor consisting of a neutron star and an evolved main-sequence star in a very faint galaxy at redshift 0.33 while Campana et al. (2011) proposed a Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…Levan et al (2011a) performed spectroscopic observations of the optical source with Gemini/GMOS on March 29, 2011, showing H β and O III emission lines (4959 and 5007 Å, respectively) at a common redshift of z = 0.353. This measurement was rapidly confirmed by independent observations with the Gran Telescopio Canarias (GTC - Thöne et al 2011). At lower energies, several radio detections were also reported: Zauderer et al (2011a) observed with the Expanded Very Large Array (EVLA) at two frequencies (1 GHz bandwidth each) centered at 4.94 and 6.69 GHz.…”
Section: The Sw 1644+57 Transient Eventmentioning
confidence: 59%
“…Levan et al (2011a) performed spectroscopic observations of the optical source with Gemini/GMOS on March 29, 2011, showing H β and O III emission lines (4959 and 5007 Å, respectively) at a common redshift of z = 0.353. This measurement was rapidly confirmed by independent observations with the Gran Telescopio Canarias (GTC - Thöne et al 2011). At lower energies, several radio detections were also reported: Zauderer et al (2011a) observed with the Expanded Very Large Array (EVLA) at two frequencies (1 GHz bandwidth each) centered at 4.94 and 6.69 GHz.…”
Section: The Sw 1644+57 Transient Eventmentioning
confidence: 59%
“…GRB101225A is an unusual GRB (its extragalactic nature has in fact been questioned; Campana et al ), with a gamma‐ray emission exceptionally long followed by a bright X‐ray transient with a hot thermal component and an unusual optical counterpart. We tested its consistency with the correlation assuming the redshift estimate from a possible supernova component in the optical LC (Thöne et al ) and the E pk from the fit of the BAT spectrum (Thöne et al ). Eγ, iso has been derived from the BAT energy assuming the scaling in fig.…”
Section: The Ex Iso −Eγ Iso −E Pk Correlationmentioning
confidence: 99%
“…GRB101225A is an unusual GRB (its extragalactic nature has been in fact questioned Campana et al 2011), with a gamma-ray emission exceptionally long followed by a bright X-ray transient with a hot thermal component and an unusual optical counterpart. We tested its consistency with the correlation assuming the redshift estimate from a possible supernova component in the optical light curve (Thöne et al 2011) and the E pk from the fit of the BAT spectrum (Thöne et al 2011). Eγ,iso has been derived from the BAT energy assuming the scaling in Fig.…”
Section: The Exiso − Eγiso − Ep K Correlationmentioning
confidence: 99%